(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
К ИСТОРИИ ЛАБОРАТОРИИ ДЕНДРОЛОГИИ ДЕНДРОЛОГИЯ ЛАБОРАТОРИЯСЫНЫН ТАРЫХЫ ON THE HISTORY OF THE DENDROLOGY LABORATORY